The Experiences of Career Transition to New Occupations Among the Retired Elderly - Kijburana, Pherarith; Nilchantuk, Chureerat; Sansa, Niranart (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This research aims to study the experiences of career transition to new occupations among the retired elderly. Utilizing a qualitative descriptive phenomenological approach, the study involved eight Thai retirees residing in Thailand, selected through purposive sampling, with in-depth interviews serving as the primary data collection tool. The findings revealed five core themes regarding these transition experiences: 1) Reasons for retirement, comprising organizational policies and regulations, family caregiving responsibilities, and personal aspirations; 2) Post-retirement career planning, involving both planned and unplanned transitions; 3) Motivations for transitioning to new occupations, including income supplementation, supporting loved ones, and pursuing dream-driven work; 4) Conditions for a successful career transition, consisting of family upbringing and experiences, professional expertise from past work, resilience against obstacles, and receiving support from family and close associates; and 5) The value and meaning of new occupations, encompassing happiness in working, providing help and care to others through work, fostering relationships, and achieving self-sufficiency. These findings provide a deeper understanding of the transition process and can serve as a guideline for psychological counseling services and the development of support systems to promote employment among the elderly.